Pengaruh Pelatihan Kewirausahaan Agribisnis terhadap Pengembangan Usaha Pertanian Kecil di Teluk Betung - Tika Leoni Putri; Ayu Dian Pratiwi Permatahati; Subandi, Subandi; Muhammad Sarifudin (CV. Creative Tugu Pena, 2021)
This study aims to analyze the impact of agribusiness entrepreneurship training on the development of small-scale farming enterprises in Teluk Betung, Bandar Lampung City. Using a quantitative descriptive approach, the research involved 30 smallholder farmers who participated in an entrepreneurship training program in 2021. Data were collected through questionnaires and analyzed using descriptive statistics and paired sample t-tests. The results showed a significant increase in participants’ knowledge, skills, and entrepreneurial motivation after the training. Notable improvements were observed in business planning, simple financial recording, market opportunity identification, and innovation in agricultural product processing. The training also fostered a more independent and market-oriented entrepreneurial mindset among participants. However, some challenges remained in post-training implementation, such as limited access to facilities and markets, as well as the lack of continuous mentoring. The study concludes that entrepreneurship training plays a vital role in strengthening smallholder farmers’ capacity and should be complemented by sustainable support systems to enhance its long-term impact.